(3GdSQGL GdefjQ aj GdEYGfI Ydi eYQaI HYV eYGfi cdGe QHfG GdMcje GdNHjQs - (3eMeO Hf CMeO GdTQHjfj, TeS GdOjf ; GdNWjH GdTQHjfj,J (B977 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQg jhfS Ydjg GdSdGe s
(3BNQgG (B:s
(3BNQg BNQ JaSjQ ShQI GdSLOI s
(3HgG fXGe GdJYbjHIs
(3YdjgG Jedc HGSe eMeO GdTjHi aGJM HjJ Gddg GdMQGes
(3hJedc YHO Gddg Hf YeQ Hf CHj HcQ Hf jMji HGYdhi SfI (B1255(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs